Young coconut juice can accelerate the healing process of cutaneous wounds - Radenahmad Nisaudah; Saleh Farid; Sayoh Ibrahim; Sawangjaroen Kitja; Subhadhirasakul Patchara; Boonyoung Piyakorn; Rundorn Wilart; Mitranun Winyou (BMC, 2012)
Abstract Background Estrogen has been reported to accelerate cutaneous wound healing. This research studies the effect of young coconut juice (YCJ), presumably containing estrogen-like substances, on cutaneous wound healing in ovairectomized rats. Methods Four groups of female rats (6 in each group) were included in this study. These included sham-operated, ovariectomized (ovx), ovx receiving estradiol benzoate (EB) injections intraperitoneally, and ovx receiving YCJ orally. Two equidistant 1-cm full-thickness skin incisional wounds were made two weeks after ovariectomy. The rats were sacrificed at the end of the third and the fourth week of the study, and their serum estradiol (E2) level was measured by chemiluminescent immunoassay. The skin was excised and examined in histological sections stained with H&E, and immunostained using anti-estrogen receptor (ER-α an ER-β) antibodies. Results Wound healing was accelerated in ovx rats receiving YCJ, as compared to controls. This was associated with significantly higher density of immunostaining for ER-α an ER-β in keratinocytes, fibroblasts, white blood cells, fat cells, sebaceous gland, skeletal muscles, and hair shafts and follicles. This was also associated with thicker epidermis and dermis, but with thinner hypodermis. In addition, the number and size of immunoreactive hair follicles for both ER-α and ER-β were the highest in the ovx+YCJ group, as compared to the ovx+EB group. Conclusions This study demonstrates that YCJ has estrogen-like characteristics, which in turn seem to have beneficial effects on cutaneous wound healing.